Lower plasma melatonin levels predict worse long-term survival in pulmonary arterial hypertension. (25th November 2020) - Cai, Z; Klein, T; Geenen, L.W; Tu, L; Tian, S; Van Den Bosch, A.E; De Rijke, Y.B; Reiss, I.K.M; Boersma, E; Duncker, D.J; Boomars, K.A; Guignabert, C; et al.
Abstract: Background: Exogenous melatonin has been reported to be beneficial in the treatment of pulmonary hypertension (PH) in animal models. Multiple mechanisms may be involved, with melatonin exerting anti-oxidant and anti-inflammatory effects, as well as inducing vasodilation and cardio-protection. However, endogenous levels of melatonin in treatment-naïve pulmonary arterial hypertension (PAH) patients and their clinical significance are still unknown. Methods and results: Plasma levels of endogenous melatonin were measured by liquid chromatography-tandem mass spectrometry in treatment-naïve PAH patients (n=43) and healthy controls (n=111). Melatonin levels were higher in PAH patients when compared with controls (Median 118.9 [IQR 109.3–147.7] versus 108.0 [102.3–115.2] pM, P<0.001) (Figure 1A). The overall mortality was 26% (11/43) during a median long-term follow-up of 42 [IQR: 32–58] months. When PAH patients were stratified into 4 groups according to the quartiles of melatonin levels, the mortality from below 1st quartile to above 4th quartile was 55% (6/11), 10% (1/10), 0% (0/12), and 40% (4/10), respectively (Figure 1B). Kaplan-Meier analysis further showed that patients with melatonin levels below the 1st quartile (<109.3 pM) had a worse long-term survival than patients with melatonin levels above the 1st quartile (Mean survival times were 46 [95% CI: 30–65] versus 68 [58–77] months, Log-rank, p=0.026) (Figure 1C). Conclusion: Endogenous melatonin levels were increased in treatment-naïve PAH patients, and lower levels of melatonin were associated with worse long-term survival in patient with PAH, however, whether exogenous melatonin supplements may be effective as a therapeutic strategy in human PAH remains to be established. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): This work was supported by the China Scholarship Council (201606230252) as well as the Netherlands CardioVascular Research Initiative: an initiative with support of the Dutch Heart Foundation (CVON2014-11, RECONNECT), and German Center for Cardiovascular Research (DZHK81Z0600207). Instrumentation support was received from AB Sciex, ltd. for LC-MS/MS analyses performed in this study.